9 to 5 Do You Know If Your Boss Knows Where You Are? Case Studies of Radio Frequency Identification Usage in the Workplace - Balkovich, Edward (RAND Corporation, 2005)
Describes a case study of six enterprises that use Radio Frequency Identification (RFID) tags to control access in the workplace to understand their policies about personally identifiable records obtained by sensing RFID-based access cards. These policies have a number of common features, but the policies are neither documented nor shared with employees. While employees ought to be informed about uses of access control system records, implementing traditional fair information practices for such records would be impractical in some situations.